Effect of food components on cytochrome P450 expression and activity - Ruoyao Sang; Wenzhao Jiang; Cai Zhang; Runting Yin; Zhen Ouyang; Yuan Wei (Human Nutrition & Metabolism)
Cytochrome P450s (CYPs) are a family of enzymes within the hemoglobin superfamily that play a crucial role in drug metabolism. CYP activity and expression exhibit considerable individual variability. In addition to genetic factors, extrinsic influences, such as food, can affect their activity and/or expression, thereby impacting the efficacy and adverse effects of drugs metabolized by these enzymes. As food variety and diversity in dietary patterns increase, food has become an increasingly significant factor in drug metabolism. This review, summarizes the effects of various foods on the activity and expression of major CYP subtypes involved in drug metabolism, offering new insights into food-drug interactions and providing references for the safe clinical use of edible and medicinal plants.